2016
DOI: 10.1007/s12185-016-2119-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of mutations in the cohesin complex in acute myeloid leukemia

Abstract: Mutations in the members of the cohesin complex have recently been identified as early events in acute myeloid leukemia (AML) pathogenesis. Studies conducted by our lab and others have shown that cohesin mutations or knockdown of cohesin subunits impair hematopoietic differentiation and enforce stem cell programs in both human and mouse hematopoiesis. Furthermore, studies in both models demonstrated global changes in chromatin accessibility and structure, in particular increased accessibility at binding sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Similarly, the downregulation of epigenetic regulators 31 36 , cohesins 37 , and splicing factors 38 , which are frequently mutated or inactivated in several myeloid malignancies, could be involved in the pathogenesis of CALR-mutated disease. Furthermore, CALR mutations seem to impair essential cellular function as protein ubiquitination and ER stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the downregulation of epigenetic regulators 31 36 , cohesins 37 , and splicing factors 38 , which are frequently mutated or inactivated in several myeloid malignancies, could be involved in the pathogenesis of CALR-mutated disease. Furthermore, CALR mutations seem to impair essential cellular function as protein ubiquitination and ER stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Cohesin is a ring-shaped complex involved in chromatin replication, organization and repair, with STAG2 acting as a core complex member and HDAC8 controlling chromatin accessibility 34 . Cohesin dysregulation has cell context-specific consequences, including DNA damage and aneuploidy; in leukemic cells, cohesin mutations are thought to enforce stem cell programs by altering chromatin organization 35 .…”
Section: Resultsmentioning
confidence: 99%
“…Proteomic analysis and subsequent validation experiments showed that DCAF15 loaded into CLR4 complexes, interacted with cohesin complex members SMC1 and SMC3, and promoted their ubiquitination. We were intrigued by these interactions given the similar CRISPR screening scoring pattern of DCAF15 to the cohesin factors STAG2 and HDAC8 (Figure 2E); the shared roles of cohesin and CRL4 E3 ligases in DNA metabolism, organization, replication and repair 34, 59, 60 ; and the ability of cohesin mutations to dysregulate hematopoietic differentiation in myeloid malignancies 35 . Rather than globally controlling SMC protein levels, we speculate that CRL4-DCAF15 complexes ubiquitinate cohesin at specific genomic sites to regulate chromatin topology or repair (Figure 7G).…”
Section: Discussionmentioning
confidence: 99%
“…103 Mice homozygous for loss-of-function mutations in core cohesin components in haematopoietic cells are embryonic lethal, while haematopoietic heterozygous knockdown of Rad21, Smc3, and Stag1 results in increased self-renewal, expansion of the immunophenotypic multipotent myeloid progenitor compartment, and impaired differentiation. [104][105][106] To varying degrees in the different models, cohesin depletion resulted in changed chromatin accessibility. In an Smc3 conditional knockout, Viny et al reported a significant decrease in a large subset of genes in cohesin haploinsufficient bone marrow cells compared with wild type, with reduced chromatin accessibility in the −30 kb to +10 kb region surrounding the transcriptional start site of downregulated genes.…”
Section: Transformation To Ml-ds: Cooperating Mutationsmentioning
confidence: 99%